1) 8(6 - x)(x+5)=0 any quadratic equation can be written in this form
a(x-x_1)(x-x_2)=0
The zero product property states that two factors either the first one or the second factor is equal to zero.
a .b =0 a=(6-x) and b =(x+5)
8(6 - x)(x+5)=0
a b
So,
(6-x) =0
x=6
(x+5)=0
x=-5
Then S ={-5,6}
------------------------------------------------------------------
Alternatively, we can prove that zero product property validity, by solving it traditionally:
Let's expand those parentheses:
8(6 - x)(x+5)=0
8(6x+30-x²-5x)=0
8(-x²-x+30)=0
-8x²-8x+240=0
-8x²-8x+240=0 Divide by -8
x² +x -30=0
Which two numbers whose sum is 1 and their product is -30?
S = _6 + -5 = 1
P = 6 x -5 = -30
Let's swap the sign
S ={-5,6}